Work-family interference among Ghanaian women in higher status occupations - Bedu-Addo, Paul Kobina Annan (2010)
Work-family interference (WFI) is becoming one of the principal hazards to occupational health, family satisfaction, well-being and job satisfaction in the 21st century, especially among women professionals. With obvious increases in female participation within the upper echelons of the labour force both in the developed and developing world (Wirth, 2000); the need to effectively combine work and family roles has become quite a critical issue in occupational and organisational psychology, as well as family studies.